Analysis of Cheiloscopy as a Means of Identification of ABO Blood Groups Among Mongoloid and Australomelanesoid Populations in Indonesia: Analisis Cheiloscopy sebagai Alat Identifikasi Golongan Darah ABO pada Populasi Mongoloid dan Australomelanesoid di Indonesia - Muhammad Yusuf Arrozhi Arrozhi; IBGd Surya Putra Pidada; Henro Widagdo; Rusyad Adi Suriyanto (Ahmad Dahlan Medical Journal, 2022)
Natural disasters and forensic cases are increasing, requiring methods to identify victims and criminal cases that are easier, more efficient, and accurate. Lip print pattern is one way to help the process of individual identification. Lip print analysis using facial photo analysis method helps identify a person's characteristics. To determine the differences in proportion and the uniqueness of the lip print patterns in relation to ABO blood group between the Mongoloid dan Australomelanesoid populations of Indonesia. A total of 124 Mongoloid and Australomelanesoid population respondents who met the inclusion criteria were included in the study consisting of 31 males and females from each population. After the respondents signed the informed consent, they were interviewed and photos of their faces and lips were taken, then lip print pattern analysis was performed. Statistical analysis using Chi Square and Cohen's Kappa test.  From 124 research respondents, the Cohen's Kappa consistency test obtained p> ​​0.8 which means it has a very good match.  The research shows that the majority of the Mongoloid population has a type I' pattern while the Australomelanesoid has a type IV pattern. The majority of the Mongoloid population has AB blood, while the majority of Australomelanesoid has O blood. There is a non-significant difference in the proportion of lip print patterns in distinguishing between ABO blood groups and the Mongoloid and Australomelanesoid populations in Indonesia.   Abstrak Bencana alam dan kasus forensik yang semakin meningkat, membutuhkan metode untuk mengidentifikasi korban dan kasus kriminal yang lebih mudah, efisien, dan akurat. Pola sidik bibir merupakan salah satu cara untuk membantu proses identifikasi individu. Analisis sidik bibir dengan metode analisis foto wajah membantu mengidentifikasi karakteristik seseorang. Tujuan dari penelitian ini adalah untuk mengetahui perbedaan proporsi dan keunikan pola sidik bibir dalam kaitannya dengan golongan darah ABO antara populasi Mongoloid dan Australomelanesoid di Indonesia. Sebanyak 124 responden populasi Mongoloid dan Australomelanesoid yang memenuhi kriteria inklusi diikutsertakan dalam penelitian, terdiri dari 31 laki-laki dan perempuan dari masing-masing populasi. Setelah responden menandatangani formulir informed consent, mereka diwawancarai, foto wajah dan bibir mereka diambil, kemudian dilakukan analisis pola sidik bibir. Untuk signifikansi statistik, data dianalisis dan dinyatakan dalam proporsi menggunakan uji konsistensi Cohen's Kappa dan uji chi-square. Dari 124 responden penelitian, uji konsistensi Cohen's Kappa diperoleh p > 0,8 yang berarti memiliki konsistensi sangat baik. Hasil penelitian menunjukkan bahwa mayoritas populasi Mongoloid memiliki pola tipe I', sedangkan Australomelanesoid memiliki pola tipe IV. Mayoritas populasi Mongoloid memiliki darah AB, sedangkan mayoritas populasi Australomelanesoid memiliki darah O. Terdapat perbedaan proporsi pola sidik bibir yang tidak bermakna dalam membedakan golongan darah ABO dengan populasi Mongoloid dan Australomelanesoid di Indonesia.